Molecular factors involved in skin dryness in diabetic patients - Narbutt, Joanna; Bednarski, Igor; Lesiak, Aleksandra (Dermatology Review/Przegląd Dermatologiczny, 2016)
Diabetes is a chronic systemic disease affecting 8.3% of the general population, thus constituting an important clinical and financial problem for healthcare systems throughout the world. Complications of diabetes damage both many internal organs and skin. Skin complications of diabetes can anticipate its clinical symptoms. Diabetic skin, irritated and dry in many cases, is susceptible to skin infections. However, there is little known about molecular changes in skin in diabetes. Many studies are concentrated on epidermal barrier damage, dysfunction of epidermis integrity and dysfunction of sebaceous glands. Another complex problem is skin care in diabetic patients. A profound understanding of cellular-level processes in diabetes could lead to the discovery of new therapy efficacy markers and new skin care products.